Des Menschens Genitive. Normabweichende Genitiv-Varianten bei schwachen Maskulina - Krischke, Wolfgang (Linguistik Online, 2013)
Abstract The genitive singular of the weak masculine nouns appears in three non-standard variations in addition to the standard suffix -(e)n: one variation is case augmenting (des Bär-en-s), one is stem affixing (des Polizist-s) and one lacks a case suffix (des Patient-Ø). Linguists as well as language critics have focussed mainly on the stem affixing genitive while more or less ignor¬ing the two other non-standard variations. This paper presents a corpus-based investigation regarding frequency and contexts of all three variations, also considering the diachronic back¬ground and the implications the results might have for predicting the further development of the declension class of the weak masculine nouns.